Unmasking the prevalence of amyloid cardiomyopathy in the real world: results from Phase 2 of the AC‐TIVE study, an Italian nationwide survey. (10th May 2022) - Merlo, Marco; Pagura, Linda; Porcari, Aldostefano; Cameli, Matteo; Vergaro, Giuseppe; Musumeci, Beatrice; Biagini, Elena; Canepa, Marco; Crotti, Lia; Imazio, Massimo; Forleo, Cinzia; Cappelli, Francesco; et al.
Abstract: Aim: To investigate the prevalence of amyloid cardiomyopathy (AC) and the diagnostic accuracy of echocardiographic red flags of AC among consecutive adult patients undergoing transthoracic echocardiogram for reason other than AC in 13 Italian institutions. Methods and results: This is an Italian prospective multicentre study, involving a clinical and instrumental work‐up to assess AC prevalence among patients ≥55 years old with an echocardiogram suggestive of AC (i.e. at least one echocardiographic red flag of AC in hypertrophic, non‐dilated left ventricles with preserved ejection fraction). The study was registered at ClinicalTrials.gov (NCT04738266). Overall, 381 patients with an echocardiogram suggestive of AC were identified among a cohort of 5315 screened subjects, and 217 patients completed the investigations. A final diagnosis of AC was made in 62 patients with an estimated prevalence of 29% (95% confidence interval 23%–35%). Transthyretin‐related AC (ATTR‐AC) was diagnosed in 51 and light chain‐related AC (AL‐AC) in 11 patients. Either apical sparing or a combination of ≥2 other echocardiographic red flags, excluding interatrial septum thickness, provided a diagnostic accuracy >70%. Conclusion: In a cohort of consecutive adults with echocardiographic findings suggestive of AC and preserved left ventricular ejection fraction, the prevalence of AC (either ATTR or AL) was 29%. Easily available echocardiographic red flags, when combined together, demonstrated good diagnostic accuracy. Abstract : Amyloid cardiomyopathy (AC) prevalence according to selected group. CKD, chronic kidney disease; CTS, carpal tunnel syndrome; FP, filling pattern; IAS, interatrial septum; IVS, interventricular septum; LV, left ventricle; LVEDVi, left ventricular end‐diastolic volume index; LVEF, left ventricular ejection fraction.